2016
DOI: 10.4012/dmj.2015-028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biocompatibility and mechanical properties of ZrO<sub>2</sub>-Al<sub>2</sub>O<sub>3</sub> ceramics composites

Abstract: This study evaluated cell viability, microhardness and flexural strength of two ceramic composites systems (ZA and AZ), pure alumina and zirconia. There were prepared homogeneous mixtures of 78wt%Al2O3+20wt%3Y-TZP+2wt%Al2O3w (AZ) and 80wt%3Y-TZP+18wt%Al2O3+2wt%Al2O3w (ZA), as well as 3Y-TZP (Z), pure Al2O3 (A) and commercial monolithic 3Y-TZP (Zc). Also mouse fibroblast cells 3T3-L1 and a MTT test was carried out at 24, 48 and 72 h. The surfaces were observed with SEM and the microhardness and three-point flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 22 publications
3
9
0
2
Order By: Relevance
“…It was observed that the ionomer had larger and more irregular particles compared to the ZrO 2 particles. These results agreed with those reported in other studies [17,34,35]. Additionally, it was observed that the ZrO 2 particles appeared as agglomerates, without any significant difference between the different granulometries.…”
Section: Resultssupporting
confidence: 93%
“…It was observed that the ionomer had larger and more irregular particles compared to the ZrO 2 particles. These results agreed with those reported in other studies [17,34,35]. Additionally, it was observed that the ZrO 2 particles appeared as agglomerates, without any significant difference between the different granulometries.…”
Section: Resultssupporting
confidence: 93%
“…Some authors have shown their cell viability for many potential applications [8,[14][15][16][17][18]. Similarly, Al 2 O 3 exhibits a biocompatible behavior and is a standard ceramic-ceramic articulation material, due to its hardness and its least wear compared to metals, it has been used as the femoral head for joint replacement through decades [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Керамические материалы на основе системы иттрий стабилизированный диоксид циркония (Y-ZrO 2 )-оксид алюминия(Al 2 O 3 ) обладают уникальными свойствами: высокой прочностью при изгибе и трещиностойкостью (Y-ZrO 2 ) в сочетании с химической инертностью и твердостью (Al 2 O 3 ), что делает их широко востребованными в качестве конструкционной и функциональной керамики [1]. Такие материалы применяются в различных областях техники: в ответственных узлах в машиностроении, в авиакосмической отрасли, для медицинских инструментов и имплантатов [2][3][4]. К недостаткам технологии такой композиционной керамики относятся: высокая температура спекания (1600-1750°С), сопровождающаяся ростом зерна [5], необходимость длительных выдержек при высокой температуре [6] либо применение дорогостоящих электроимпульсного плазменного спекания [7] или горячего прессования [8].…”
Section: Introductionunclassified